(untitled) (Forum Agribisnis, 2017)
Indonesia should focus on cocoa products that have the highest competitiveness in order to compete with other competitors in cocoa international trade. This research aimed to analyze Indonesia’s cocoa and cocoa preparations competitiveness. Data used in this research were secondary data. Research began with analyzed cocoa and cocoa preparations market structure. The result showed that the market structure of cocoa paste, cocoa butter and cocoa powder (unsweetened) classified as an oligopoly, in the other hand cocoa beans classified as monopoly. RCA (Revealed Comparative Advantage) method showed that Indonesia had comparative advantages on cocoa beans, cocoa paste and cocoa butter (RCA>1). TSI (Trade Specialization Index) method showed that Indonesia had a tendency as a net exporter of cocoa beans, cocoa paste and cocoa butter. EPD (Export Products Dynamic) method showed that Indonesia had a high competitive advantages on cocoa beans, cocoa paste, cocoa butter and cocoa powder (unsweetened).